Test-Retest, Inter-Rater and Intra-Rater Reliability for Spatiotemporal Gait Parameters Using SANE (an eaSy gAit aNalysis systEm) as Measuring Instrument - Betsy Dayana Marcela Chaparro Rico (Applied Sciences, 2020)
Studies have demonstrated the validity of Kinect-based systems to measure spatiotemporal parameters of gait. However, few studies have addressed test-retest, inter-rater and intra-rater reliability for spatiotemporal gait parameters. This study aims to assess test-retest, inter-rater and intra-rater reliability of SANE (eaSy gAit aNalysis system) as a measuring instrument for spatiotemporal gait parameters. SANE comprises a depth sensor and a software that automatically estimates spatiotemporal gait parameters using distances between ankles without the need to manually indicate where each gait cycle begins and ends. Gait analysis was conducted by 2 evaluators for 12 healthy subjects during 4 sessions. The reliability was evaluated using Intraclass Correlation Coefficients (ICC). In addition, the Standard Error of the Measurement (SEM), and Smallest Detectable Change (SDC) was calculated. SANE showed from an acceptable to an excellent test-retest, inter-rater and intra-rater reliability; test-retest reliability ranged from 0.62 to 0.81, inter-rater reliability ranged from 0.70 to 0.95 and intra-rater ranged from 0.74 to 0.92. The subject behavior had a greater effect on the reliability of SANE than the evaluator performance. The reliability values of SANE were comparable with other similar studies. SANE, as a feasible and markerless system, has large potential for assessing spatiotemporal gait parameters.